O starości i jej uciążliwościach w Speculum naturale Wincentego z Beauvais (ok. 1194-1264) - Wojciechowska, Beata (Saeculum Christianum. Pismo Historyczne, 2016)
The stages of human life and the corresponding physiological changes have been described in many ways since ancient times. Although old age was characterized by physical and mental weakening (senility), it was portrayed as an age of wisdom which contrasted youth dominated by passions. Vincent of Beauvais devoted a few extensive chapters of Speculum naturale to the last stage of life and cited works of Cicero, Aristotle, Horace, Virgil, St. Jerome, St. Ambrose, Avicenna, Isidore of Seville, which gave him a place in the intellectual tradition of his era. According to him, the advantages of old age were moderation in pleasures, lower libido, wisdom, maturity of advice, common sense and reconciliation to death. The negative aspects of senility were diseases, discouragement and drowsiness. The physical weakness of the body affected the stability of mind. Vincent recognized old age as a natural period in human life and characterized it from the philosophical and medical points of view. He chose those pieces of writings which he considered important and representing different aspects of old age. He advised on nutrition, strengthening of the body and mental energy. Vincent emphasized that old age should be considered as fate. Therefore, there is no reason to fall in despair and wallow in hopelessness, but prepare for death through a wise life.